Development of a Mindfulness Intervention Guide as an Effort to Optimize Self-Love to Maintain Student Mental Health - Puswiartika, Dhevy; Ratu, Bau; Gagaramusu, Yusdin; Hasan, Hasan; Amiruddin, Amiruddin; Inayah, Putri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
This research aimed to develop a mindfulness intervention guide and test the effectiveness of implementing the mindfulness intervention guide as an effort to optimize self-love to maintain college students' mental health. The research method was the research and development model. This research and development procedure includes 1) the preparation stage, 2) the implementation stage, namely preparing a product draft, and 3) product testing, product validation, and preparation of the final product. This product was tested and validated by a team of experts in the field of psychology. In the implementation phase of the mindfulness intervention guide, the researchers assessed the respondents' mental health before and after administering the mindfulness intervention. Research data was analyzed descriptively, quantitatively, and qualitatively. This research showed that the intervention guide had been developed validly regarding usefulness, accuracy, suitability, and ease of guidance in implementing college student mindfulness interventions. This study also showed increased mental health levels in college students after providing mindfulness intervention to optimize self-love to maintain students' mental health. This research implied that lecturers and college students could use this mindfulness intervention guide for optimizing self-love on a limited basis to maintain daily mental health. Apart from that, this intervention guide can also be widely used by various practitioners in the mental health field, such as psychologists, counselors, guidance and counseling teachers, and social workers.